205k views
7 votes
Solve the equation 2x(2-6)=4(3+1x-2)​

User Regisbsb
by
4.6k points

2 Answers

3 votes

Answer:


x = - (1)/(3)

Explanation:

1) Simplify 2 - 6 to -4.


2x * - 4 = 4(3 + 1 * x - 2)

2) Simplify 1 × x to x.


2x * - 4 = 4(3 + x - 2)

3) Simplify 3 + x - 2 to x + 1.


2x * - 4 = 4(x + 1)

4) Simplify 2x × -4 to -8x.


- 8x = 4(x + 1)

5) Divide both sides by 4.


- 2x = x + 1

6) Subtract x from both sides.


- 2x - x = 1

7) Simplify -2x - x to -3x.


- 3x = 1

8) Divide both sides by -3.


x = - (1)/(3)

Therefor, the answer is x = -1/3.

User Gent Ahmeti
by
5.0k points
11 votes

Answer:

no solution

Explanation:

if you distribute and simplify:

4x-12 = 12+4x-8

4x-12 = 4x+4

-12 ≠ 4

User Meanman
by
4.7k points